Evaluating the ultrapoor graduation program in Somalia - Leight, Jessica; Karachiwalla, Naureen; Hirvonen, Kalle; Whittemore, Caitlin; Mugobo, Andrew; Balcha, Asrat Bekele (CGIAR System Organization, 2024)
Generate evidence around the effectiveness of the ultra-poor graduation model for an urban displaced population in Baidoa, Somalia.